Precise engineering of Gemcitabine prodrug cocktails into single polymeric nanoparticles delivery for metastatic thyroid cancer cells - Chenggong Liu; Qiongmei Han; Hua Liu; Cuirong Zhu; Wei Gui; Xiaodong Yang; Wansen Li (Taylor & Francis Group, 2020)
GLOBOCAN estimates 36 types of cancers in 185 countries based on the incidence, mortality, and prevalence in the year 2019. Nowadays, chemotherapy is the most widely used cancer treatment among immune, radio, hormone, and gene therapies. Here, we describe a very simple yet cost-effective approach that synergistically combines drug reconstitution, supramolecular nano-assembly, and tumor-specific targeting to address the multiple challenges posed by the delivery of the chemotherapeutic Gemcitabine (GEM) drug. The GEM prodrugs were gifted to impulsively self-assemble into excellent steady nanoparticles size on covalent conjugation of linoleic acid hydrophobic through amide group with ∼100 nm. Newly synthesized GEM-NPs morphology was confirmed by various electron microscopic techniques. After successful synthesis, we have evaluated the anticancer property of GEM and GEM-NPs against B-CPAP (papillary thyroid carcinoma) and FTC-133 (human follicular thyroid carcinoma) cancer cell lines. Further studies such as AO-EB (acridine orange-ethidium bromide), nuclear staining and flow cytometry analyses on cell death mechanism signified that the cytotoxicity was associated with apoptosis in thyroid cancer cells. GEM-NPs show excellent biocompatibility compared to GEM. The present study explained that GEM-NPs as a safe and hopeful strategy for chemotherapeutics of thyroid cancer therapy and deserve for further clinical evaluations.